Rudists from the Cenomanian bioherms of Hrušica and Nanos, Slovenia - Pleničar, Mario; Jurkovšek, Bogdan (Geologija, 1999)
In the paper Cenomanian rudists from Hrušica and Nanos are presented and 11 rudist species belonging to genera Caprina, Caprinula, Neocaprina, Orthoptychus, Ichthyosarcolites, Eoradiolites and Toucasia are described. Of the accompanying fossils representatives of genera Chondrodonta, Lopha (Alectryonia) and Neithea are documented. Since the wider area of rudist bioherms of the Hrušica nappe is still under study, these beds have been temporarily attributed to the Hrušica member.